Implantación de un sistema contable en la “Ferretería Jara” en la ciudad Francisco de Orellana en el periodo abril a junio de 2012 - Duman Lliguichuzca, Jorge Italo (2015)
The research paperentitled "IMPLEMENTATION OF AN ACCOUNTINGSYSTEM INTHEHARDWAREJARAFRANCISCOCITYOFOrellanaIN THE PERIODAPRIL TOJUNE 2012". It allowed me toprovideapractical solutionin improvingthe existing problemsin the business venturea studywherenoone really knowsthe economic and financialsituation thatis going through, so you coulddeterminewhat your values arebothcostsand revenue, which was learnedthrough theresults of its managementwiththe implementationof the accounting process, andthus fulfillthe prerequisite forobtainingengineering degreein Accounting and Auditing, CPA., according to the rulesNational UniversityofLoja. The thesiswas developed withthe use oftechniques andmethods besidesusinglibrary materials, interviews, virtualsourcematerialaccounting recordsof transactions madeby the companydocuments. The objectiveswere metin full at thebeginning of the investigation, raising the initial inventoryof goods, physical findingsforthe State ofInitial Situation, registering economic movementsduring theperiod Aprilto June2012, andproceededto orderverify alldocumentation andaPlanandAccounting Manualwas developedto implement theAccounting Processtodeterminethe financial statementsfor decision-making